Analyzing the Use of the Grounded Theory (GT) in Researches by Comparing Glaser and Strauss’s Version of GT - Edwina, Mariann; McDonald, Sakenya D. (International Journal of Psychosocial Rehabilitation, 2020)
This article focuses on the use of the Grounded theory (GT) in English language acquisition related researches. It will deeply discuss the processes that take place when research is conducted using GT and compare the most prominent types of GT, as introduced by Glaser and Strauss. Although there have been few discussions on how the two types differ, this article will elucidate the differences on how they are used. This article also investigates all possible GT processes or steps providing in-depth explanation for each step. It is crucial for researchers to determine the type of GT that is suitable for their study and the steps to be followed as there are many differences in the two types. As observed in many studies, this article will also discuss the advantages and limitations of using the GT. It is prominent that most researchers use GT to conduct their research for a long duration to get in-depth information to form a grounded or proved theory. Later, follow up studies are usually conducted to test the theory that has been found. Therefore, knowing what takes place in the GT and grasping the recommendation that will be given to use it effectively will help researchers plan and conduct their studies related to GT resourcefully.